1984
DOI: 10.1111/j.1476-5381.1984.tb10109.x
|View full text |Cite
|
Sign up to set email alerts
|

Tolbutamide as a model drug for the study of enzyme induction and enzyme inhibition in the rat

Abstract: 1 The effects of various drugs on the pharmacokinetics of tolbutamide have been examined in the rat.2 Phenobarbitone pretreatment caused a significant decrease in half life and area under the curve (AUC) and a significant increase in clearance and volume of distribution (Vd). 3 Acute administration of primaquine significantly increased half life and AUC and decreased clearance. In contrast, the related animoquinolone chloroquine, was without effect. 4 Acute administration of cimetidine produced similar changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

1986
1986
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…Samples were analyzed for the parent compound (tolbutamide) and its metabolites (carboxy-and hydroxytolbutamide) by means of a validated, slightly modified HPLC method (Back et al, 1984). In short, the sandwich samples (0.5 ml) were thawed, and 1.5 ml of a collagenase-Krebs' solution (100U/ml) was added.…”
Section: Methodsmentioning
confidence: 99%
“…Samples were analyzed for the parent compound (tolbutamide) and its metabolites (carboxy-and hydroxytolbutamide) by means of a validated, slightly modified HPLC method (Back et al, 1984). In short, the sandwich samples (0.5 ml) were thawed, and 1.5 ml of a collagenase-Krebs' solution (100U/ml) was added.…”
Section: Methodsmentioning
confidence: 99%
“…as previously described (Back et al, 1984) except that a ,u-Bondapak C-18 radial compression cartridge was used instead of an ODS-2 reversed-phase column. The mobile phase was a mixture of 0.05% phosphoric acid and methanol (50: 50).…”
Section: Methodsmentioning
confidence: 99%
“…A number of drug interactions with tolbutamide have been reported (Hansen & Christensen, 1977) and Back et al (1984) have demonstrated that tolbutamide is a good marker drug for assessing drug interactions in vivo. The most studied interaction is that with the sulphonamide, sulphaphenazole, which is known to increase the half-life of tolbutamide in man by up to 8 fold (Christensen et al, 1963;Schulz & Schmidt, 1970;Pond et al, 1977).…”
Section: Introductionmentioning
confidence: 99%
“…4-Hydroxytolbutamide was quantified by h.p.l.c. as previously described (Back et al, 1984) using a reversedphase column (ODS-2) and a mobile phase of 0.05% phosphoric acid and methanol (50:50). The coefficient of variation of 4-hydroxytolbutamide was 4.9% at a concentration of 3.5 ,ug ml-' for the entire extraction procedure.…”
Section: Introductionmentioning
confidence: 99%